2009
DOI: 10.1002/oa.1096
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ante mortem trauma in three modern skeletal populations

Abstract: When archaeological skeletons are assessed, the incidences of trauma are important. The number of fractures observed is interpreted in order to gain insight into the occurrence of interpersonal violence, workload, living conditions, etc. However, the question remains as to how these results should be interpreted -i.e., what constitutes high or low levels of trauma. The aim of this study was to investigate the occurrence of trauma in a population of modern Greeks living on Crete, as well as South African (SA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The Hamann-Todd Human Osteological Collection (HT) is an early 20th century U.S. skeletal collection, and is housed at the Cleveland Museum of Natural History, Ohio, USA (Mensforth and Latimer, 1989). The Pretoria Bone Collection (PBC) contains the remains of individuals who died in the late 20 th century, and is held in the Department of Anatomy at the University of Pretoria, South Africa (Steyn et al, 2010). The historic St. Bride's Documented Skeletal Collection (SB) dates from the 18th to 19th centuries (Scheuer and Black, 1995), and is still housed in the crypt of St. Bride's Church, Fleet Street, London, UK.…”
Section: Methodsmentioning
confidence: 99%
“…The Hamann-Todd Human Osteological Collection (HT) is an early 20th century U.S. skeletal collection, and is housed at the Cleveland Museum of Natural History, Ohio, USA (Mensforth and Latimer, 1989). The Pretoria Bone Collection (PBC) contains the remains of individuals who died in the late 20 th century, and is held in the Department of Anatomy at the University of Pretoria, South Africa (Steyn et al, 2010). The historic St. Bride's Documented Skeletal Collection (SB) dates from the 18th to 19th centuries (Scheuer and Black, 1995), and is still housed in the crypt of St. Bride's Church, Fleet Street, London, UK.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of these papers analyze historical collections (Assis et al 2011;Capasso 2007;Crist and Sorg 2014;Palubeckait_ e et al 2006) or collections associated with historically significant events (Geber and Murphy 2012;Mitchell 2006), which define the short duration of use. Several adopt a forensics perspective on trauma analysis using modern or near-modern collections (Nagaoka 2012;Steyn et al 2010;van der Merwe et al 2010). These papers are not relevant to the Osteological Paradox.…”
Section: Leveraging Archaeological Contextmentioning
confidence: 99%
“…For example, although Steyn et al . () identified IRs in their sample of modern skeletal material, they excluded injuries to the dentition, extremities, and sternum and therefore, likely under‐estimated the number of IRs present. Until quite recently, the thorax, extremities, and dentition were ignored during analysis, although injuries to these regions are ubiquitous in clinical trauma studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our ability to identify past individuals with multiple injuries is directly influenced by which skeletal, and dental changes are considered to be traumatic, and how these data are recorded (Judd, 2002;Judd & Redfern, 2012). For example, although Steyn et al (2010) identified IRs in their sample of modern skeletal material, they excluded injuries to the dentition, extremities, and sternum and therefore, likely under-estimated the number of IRs present. Until quite recently, the thorax, extremities, and dentition were ignored during analysis, although injuries to these regions are ubiquitous in clinical trauma studies (e.g.…”
Section: Problems and Limitations For Multiple Injury Analysis In Ostmentioning
confidence: 99%